1984
DOI: 10.1002/macp.1984.021850211
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation by synthesis of semi‐interpenetrating network on the basis of polystyrene and poly(butyl methacrylate) from homogeneous solution

Abstract: Phase separation by semi-interpenetrating polymeric network formation based on the copolymer styrene-divinylbenzene (PS-DVB) and poly(buty1 methacrylate) (PBMA) was investigated by light scattering. The time for phase separation was measured as a function of the rate of the copolymerization reaction and of the composition of the initial blend. The time until the outset of phase separation decreases with increasing content of PBMA in the blend. The change in concentration of DVB does not influence the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…37,38 Incomplete phase separation in a fully formed IPN or semi-IPN leads to the appearance of interphase or transitive regions, which have more "defect" and porous structure as compared to the structure of pure individual components of IPN. [38][39][40][41][42][43] The semi-IPN represents a four-phase system consisting of microregions of the copolymer, microregions of the linear polymer (PEG), microregions of the copolymer enriched with the linear polymer, and microregions of the linear polymer enriched with the copolymer. Apparently, extraction of the linear polymer from the different regions of the polymerized membranes will result in formation of pores with wide size distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Incomplete phase separation in a fully formed IPN or semi-IPN leads to the appearance of interphase or transitive regions, which have more "defect" and porous structure as compared to the structure of pure individual components of IPN. [38][39][40][41][42][43] The semi-IPN represents a four-phase system consisting of microregions of the copolymer, microregions of the linear polymer (PEG), microregions of the copolymer enriched with the linear polymer, and microregions of the linear polymer enriched with the copolymer. Apparently, extraction of the linear polymer from the different regions of the polymerized membranes will result in formation of pores with wide size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the high molecular weight of PEG used in this system, the phase separation is not complete. Therefore, heterogeneous microphase nonequillibrium structures are formed that remain stable for an unlimited time, creating a semiinterpenetrating polymer network (semi-IPN) between the cross-linked copolymer and poly(ethylene glycol). , Incomplete phase separation in a fully formed IPN or semi-IPN leads to the appearance of interphase or transitive regions, which have more “defect” and porous structure as compared to the structure of pure individual components of IPN. The semi-IPN represents a four-phase system consisting of microregions of the copolymer, microregions of the linear polymer (PEG), microregions of the copolymer enriched with the linear polymer, and microregions of the linear polymer enriched with the copolymer. Apparently, extraction of the linear polymer from the different regions of the polymerized membranes will result in formation of pores with wide size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have used TRAMS to enhance our understanding of the factors which govern the stability of aqueous water‐borne polymeric dispersions, including acrylic latices 13. These systems have, in turn, prompted our interest in poly(butyl methacrylate) (PBMA), a technologically important polymer which has found application in a variety of complex systems ranging from interpenetrating polymer networks14, 15 and polymer blends16, 17 to aqueous polymeric dispersions for use in the coatings industry 18, 19. As a prelude to investigating the solution morphology and film‐forming characteristics of a series of fluorescently labelled PBMA latex particles,13 we report here upon studies of the dynamic behaviour of linear samples of PBMA, in dilute solution, using fluorescence‐quenching and anisotropy measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Sperling et al,[5][6][7]9 and Lipatov. 10 There is splendid scientific literature concerning IPN's based on polyurethanes 11 and epoxy resins. 12 Reza et al 13 have reported the synthesis and morphology of IPN's containing copolymers of methylene-bisacrylamide and vinyl ferrocene.…”
mentioning
confidence: 99%